Biomechanical differences in the sprint start between faster and slower high-level sprinters - Coh, M.; Peharec, S.; Bacic, P.; Mackala, K. (Journal of Human Kinetics, 2017)
The purpose of this study was to examine the kinematic and kinetic differences of the sprint start and first two steps between faster and slower high-level sprinters. Twelve male sprinters were dichotomized according to personal best 60- and 100-m times. Each participant performed five starts under constant conditions. An eight-camera system was used for 3-D kinematic analysis. Dynamic forces at the start were determined with starting blocks mounted on bipedal force plates. Measures of front and rear block total force, front and rear block maximal force, time to front and rear block peak force, total force impulse, total horizontal and vertical impulse, front and rear block force impulse, time of block clearance, block leaving velocity and block leaving acceleration were collected. Between-group comparisons were made using independent samples t tests (p < 0.05) and by calculating effect sizes (Cohen`s d). Spearman`s correlation coefficients were used to examine the relationships between sprint start kinematics, kinetic measures and sprint performance. Significant between-group differences were observed in rear block total force (p = 0.0059), rear block maximal vertical force (p = 0.0037) and total force impulse (p = 0.0493). Only front block total force significantly correlated with 100 m sprint performance in both the slower and faster groups (r = 0.94 and 0.54, respectively; p = 0.05). Our findings suggest that faster sprinters show enhanced sprint start motor performance with greater force development than slower sprinters.